2014
DOI: 10.1080/00268976.2013.874600
|View full text |Cite
|
Sign up to set email alerts
|

The influence of orbital rotation on the energy of closed-shell wavefunctions

Abstract: The orbital dependence of closed-shell wavefunction energies is investigated by performing doublyoccupied configuration interaction (DOCI) calculations, representing the most general class of these wavefunctions. Different local minima are examined for planar hydrogen clusters containing two, four, and six electrons applying (spin) symmetry-broken restricted, unrestricted and generalized orbitals with real and complex coefficients. Contrary to Hartree-Fock (HF), restricted DOCI is found to properly break bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(126 citation statements)
references
References 28 publications
2
124
0
Order By: Relevance
“…Prior work has found good agreement generally, [9,11,12] but also some important discrepancies. [38,39] We wish to address this question for system sizes out of reach (due to computational demands) of conventional seniority zero FCI.…”
Section: Energy Comparison Between Doci and Pccdmentioning
confidence: 81%
“…Prior work has found good agreement generally, [9,11,12] but also some important discrepancies. [38,39] We wish to address this question for system sizes out of reach (due to computational demands) of conventional seniority zero FCI.…”
Section: Energy Comparison Between Doci and Pccdmentioning
confidence: 81%
“…Limacher et al 17 have shown that the basisdependent DOCI energy surface has many local minima. To cope with those local minimum problems, we now introduce an orbital optimisation algorithm tailored at locating the global energy minimum.…”
Section: B Orbital Optimisation Algorithmsmentioning
confidence: 99%
“…This method performs particularly well when there are many local energy minima, as in the case of DOCI wave functions. 17 The work flow for the SA procedure pertaining to the orbital optimisation of CI methods is depicted in Fig. 2.…”
Section: Energy Based Orbital Optimisation Through Simulated Annealingmentioning
confidence: 99%
“…A different, computationally feasible approach suitable for strongly-correlated systems uses seniority-zero wavefunctions to describe the static/nondynamic part of the electron correlation en-ergy. [31][32][33][34][35][36][37][38][39][40][41][42][43][44] The missing dynamic electron correlation effects are included a posteriori in these ansätze using, for instance, many-body perturbation theory [45][46][47], coupled-cluster theory [48][49][50][51][52], extended random phase approximation [53], and density functional theory (DFT) corrections [54,55].…”
Section: Introductionmentioning
confidence: 99%